1998
DOI: 10.1090/s0002-9947-98-02063-7
|View full text |Cite
|
Sign up to set email alerts
|

Abelian subgroups of pro-$p$ Galois groups

Abstract: Abstract. It is proved that non-trivial normal abelian subgroups of the Galois group of the maximal Galois p-extension of a field F (where p is an odd prime) arise from p-henselian valuations with non-p-divisible value group, provided #(Ḟ /Ḟ p ) ≥ p 2 and F contains a primitive p-th root of unity. Also, a generalization to arbitrary prime-closed Galois-extensions is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…As a corollary of Theorem 1.4, we obtain yet another well-known result on maximal pro-p Galois groups due to Engler and Nogueira [15] (for p = 2) and Engler and Koenigsmann [14] (for p > 2).…”
Section: Our First Substantial Results Issupporting
confidence: 58%
“…As a corollary of Theorem 1.4, we obtain yet another well-known result on maximal pro-p Galois groups due to Engler and Nogueira [15] (for p = 2) and Engler and Koenigsmann [14] (for p > 2).…”
Section: Our First Substantial Results Issupporting
confidence: 58%
“…(An element of the form n a + m √ b, with a, b ∈ F {0} and n, m > 1 is, for instance, nested.) This improves the following result: the Galois group of the maximal p-extension F (p)/F is a solvable group if and only if the field F is p-rigid (proved first in [EK98]).…”
Section: Introductionsupporting
confidence: 54%
“…In Galois theory one has the following result, due to A. Engler, J. Koenigsmann and J. Nogueira (cf. [10] and [11]). Theorem 3.2 Let K be a field containing a root of 1 of order p (and also √ −1 if p = 2), and suppose that the maximal pro-p Galois group G K (p) of K is not isomorphic to Z p .…”
Section: 2mentioning
confidence: 98%
“…This subgroup is abelian, and normal in G. In [11], A. Engler and J. Koenigsmann showed that if the maximal pro-p Galois group G K (p) of a field K is not cyclic then it has a unique maximal normal abelian closed subgroup (i.e., one containing all normal abelian closed subgroups of G K (p)), which coincides with the θ K -center Z(G K ), and the short exact sequence of pro-p groups…”
Section: Quadrellimentioning
confidence: 99%